The rarity of ALDH+ cells is the key to separation of normal versus leukemia stem cells by ALDH activity in AML patients - Hoang, Thanh Van; Buß, Eike Christian; Wang, Wenwen; Hoffmann, Isabel; Raffel, Simon; Zepeda-Moreno, Abraham; Baran, Natalia; Wuchter, Patrick; Eckstein, Volker; Trumpp, Andreas; Jauch, Anna; Ho, Anthony Dick; et al. (International journal of cancer, 2015)
To understand the precise disease driving mechanisms in acute myeloid leukemia (AML), comparison of patient matched hematopoietic stem cells (HSC) and leukemia stem cells (LSC) is essential. In this analysis, we have examined the value of aldehyde dehydrogenase (ALDH) activity in combination with CD34 expression for the separation of HSC from LSC in 104 patients with de novo AML. The majority of AML patients (80 out of 104) had low percentages of cells with high ALDH activity (ALDH+ cells; <1.9%; ALDH-rare AML), whereas 24 patients had relatively numerous ALDH+ cells (≥1.9%; ALDH-numerous AML). In patients with ALDH-rare AML, normal HSC could be separated by their CD34+ALDH+ phenotype, whereas LSC were exclusively detected among CD34+ALDH− cells. For patients with ALDH-numerous AML, the CD34+ALDH+ subset consisted mainly of LSC and separation from HSC was not feasible. Functional analyses further showed that ALDH+ cells from ALDH-numerous AML were quiescent, refractory to ARA-C treatment and capable of leukemic engraftment in a xenogenic mouse transplantation model. Clinically, resistance to chemotherapy and poor long-term outcome were also characteristic for patients with ALDH-numerous AML providing an additional risk-stratification tool. The difference in spectrum and relevance of ALDH activity in the putative LSC populations demonstrates, in addition to phenotypic and genetic, also functional heterogeneity of leukemic cells and suggests divergent roles for ALDH activity in normal HSC versus LSC. By acknowledging these differences our study provides a new and useful tool for prospective identification of AML cases in which separation of HSC from LSC is possible.
Online: 26 Dec 2014
Gesehen am 07.09.2020